2009
DOI: 10.1074/jbc.m807637200
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3:Shc Scaffolds Integrate Phosphoserine and Phosphotyrosine Signaling to Regulate Phosphatidylinositol 3-Kinase Activation and Cell Survival

Abstract: Integrated cascades of protein tyrosine and serine/threonine phosphorylation play essential roles in transducing signals in response to growth factors and cytokines. How adaptor or scaffold proteins assemble signaling complexes through both phosphotyrosine and phosphoserine/threonine residues to regulate specific signaling pathways and biological responses is unclear. We show in multiple cell types that endogenous 14-3-3 is phosphorylated on Tyr 179 in response to granulocyte macrophage colony-stimulating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 33 publications
3
42
0
Order By: Relevance
“…25 Thus, 14 --3 --3s is not likely to participate in the activation of pro-survival signaling downstream of the ShcA SH2 domain. We further demonstrate that 14 --3 --3z specifically co-immunoprecipitates with wild-type ShcA, and not the ShcR397K mutant, in mammary tumor lysates, which is consistent with the observation that 14 --3 --3z activates the PI3K/AKT pathway by recruiting the p85 regulatory subunit 19,26 (Figure 4d). However, we cannot exclude the possibility that one or more of the remaining 14 --3 --3 family members are recruited to the SH2 domain of ShcA to enhance breast cancer cell survival.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…25 Thus, 14 --3 --3s is not likely to participate in the activation of pro-survival signaling downstream of the ShcA SH2 domain. We further demonstrate that 14 --3 --3z specifically co-immunoprecipitates with wild-type ShcA, and not the ShcR397K mutant, in mammary tumor lysates, which is consistent with the observation that 14 --3 --3z activates the PI3K/AKT pathway by recruiting the p85 regulatory subunit 19,26 (Figure 4d). However, we cannot exclude the possibility that one or more of the remaining 14 --3 --3 family members are recruited to the SH2 domain of ShcA to enhance breast cancer cell survival.…”
Section: Resultssupporting
confidence: 74%
“…39 --40 Moreover, the ShcA SH2 domain binds Y179 of 14 --3 --3z and mutation of the ShcAbinding site (Y179F) significantly reduced AKT activation and survival of a hematopoietic cell line. 19 Thus we propose that the ShcA SH2 domain binds tyrosine phosphorylation sites within 14 --3--3z, and potentially also 14 --3 --3b, to indirectly recruit p85a-PI3K to the plasma membrane, leading to activation of PI3 0 K/AKTmediated survival signaling responses. Future studies with mice carrying mutant members of 14 --3 --3 family should allow this issue to be addressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be determined whether 14-3-3ζ is critical in the regulation of cell survival. The above evidence suggests that 14-3-3 proteins serve as unique integration points to coordinate kinase activity and phospho-dependent survival cues [18]. Therefore, we tested the hypothesis that 14-3-3 proteins are essential for coordinating beta cell survival as the core of a signalling node that integrates multiple survival signals.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure of 14-3-3ζ : AANAT revealed that in addition to the phosphorylation-dependent interaction through its canonical ligand-binding groove, 14-3-3 also makes extensive contacts with AANAT via other regions of the 14-3-3 channel, although these contacts must be insufficient to form a stable complex (Obsil et al, 2001). Moreover, a recent finding by can directly interact with other proteins outside of the canonical binding groove, providing a possible molecular basis for the scaffolding function of 14-3-3 (Barry et al, 2009). 14-3-3 undergoes phosphorylation at tyrosine 179 upon cytokine stimulation and this leads to the binding of Shc protein through its SH2 domain that recognizes phosphorylated tyrosine.…”
Section: Scaffoldingmentioning
confidence: 99%